Viewpoint: service research priorities – bridging the academic and practitioner perspectives. Issue 5 (5th September 2019) - Aksoy, Lerzan; Guilloux, Loïc; Duneigre, Hélène; Keita, Sikaar
Abstract : Purpose: As an interdisciplinary and applied discipline, managerial relevance has always been at the forefront of service research. This viewpoint article synthesizes the main ideas presented in one of the 10th SERVSIG conference panels by three practitioners about what they view as the biggest opportunities/challenges they face and two journal editors on current academic research priorities. The purpose of this study is to use this panel as a starting point to bridge more closely the world of academia with practice and propose a collection of recommendations toward this goal. Design/methodology/approach: This study synthesizes the academic and practitioner viewpoints presented and research conducted into research priorities. Findings: Although there is significant overlap in what is deemed important by the presenting academics and practitioners, there are some important differences when it comes to issues deemed important, how they are articulated and the language that is used. Originality/value: This paper contributes to the literature and practitioner community by summarizing the viewpoints of the two sides and curating a collection of existing approaches and new recommendations to more closely bridge academic and practitioner perspectives.